Difficult colonoscopies in the propofol era - Cardin Fabrizio; Minicuci Nadia; Campigotto Federico; Andreotti Alessandra; Granziaera Elisa; Donà Barbara; Martella Bruno; Terranova Claudio; Militello Carmelo (BMC Surgery, 2012)
Abstract Background To study the relationship between endoscopic practice and adverse events during colonoscopy under standard deep sedation induced and monitored by an anesthetist. Methods We investigated the routine activity of an endoscopy center at the Padova University teaching hospital. We considered not only endoscopic and cardiorespiratory complications, but also the need to use high-dose propofol to complete the procedure, and the inability to complete the procedure. Variables relating to the patient’s clinical conditions, bowel preparation, the endoscopist’s and the anesthetist’s experience, and the duration of the procedure were input in the model. Results 617 procedures under deep sedation were performed with a 5% rate of adverse events. The average dose of propofol used was 2.6±1.2 mg/kg. In all, 14 endoscopists and 42 anesthetists were involved in the procedures. The logistic regression analysis identified female gender (OR=2.3), having the colonoscopy performed by a less experienced endoscopist (OR=1.9), inadequate bowel preparation (OR=3.2) and a procedure lasting longer than 17.5 minutes (OR=1.6) as the main risk factors for complications. An ASA score of 2 carried a 50% risk reduction (OR=0.5). Discussion and conclusions Our model showed that none of the variables relating to anesthesiological issues influenced which procedures would prove difficult.